Thermodynamic analysis of energy storage supported multigeneration system. Issue 1 (29th April 2019) - Okonkwo, Eric C.; Adedeji, Michael J.; Abid, Muhammad; Ratlamwala, Tahir A. H.
Abstract: This article investigates the thermodynamic performance of a solar‐powered integrated multigeneration system with thermal storage. It aims at evaluating the effect of thermal storage on the overall performance of a multigeneration system. A solar heliostat field system, thermal energy storage, Rankine power cycle, electrolyzer, and a double effect absorption chiller make up the multigeneration system. Energy and exergy analyses of the system are performed, and the energy and exergy efficiencies are found to be 35.03% and 27.9%, respectively. The solar heliostat and receiver system obtained 3500 kW of heat, the thermal storage system had a thermal efficiency of 87.4% with the capacity to store 2700 kWth energy for 12 hours, the Rankine cycle produced 1068 kW of electricity and the electrolyzer which receives 20% of the net power produced was able to generate 0.0009035 kg/s of hydrogen. The absorption chiller also produced 271.9 kW of cooling. Furthermore, a parametric study was carried out to observe the effect of varying factors like direct normal irradiance (DNI), the mass fraction of the steam bled from the turbine ( j ), the pressure of the high‐temperature generator (HTG) inlet steam, and a combination of the DNI and the pressure of the HTG inlet steam on the system performance. While an increase in the DNI led to an improved thermal and exergetic efficiency, the addition of storage led to an increase of 27.7% in the utilization factor of the multigeneration system which means that the performance of the system is increased over time. Abstract :